Loading the tumor with 31P, 63Cu and 89Y provides an in vivo prompt gamma-based range verification for therapeutic protons - Cartechini, Giorgio; Fogazzi, Elena; Hart, Shanyn-Dee; Pellegri, Luna; Vanstalle, Marie; Marafini, Michela; La Tessa, Chiara (Frontiers in Physics, 2023)
In this work, we present a feasibility study for a strategy to achieve in vivo proton range verification based on prompt gammas (PG). This approach relies on the detection of signature PGs, generated by the interaction of primary protons with a non-radioactive element, that is selectively loaded into a tumor with a drug carrier. The number of characteristic gammas is directly related to the proton range, and its measurement provides an estimate of the position at which the primary beam stops with respect to tumor location. We identified 31-Phosphorous, 63-Copper and 89-Yttrium as potential candidates for this application, and carried out an experimental campaign to characterize their PG spectrum emitted after irradiation with clinical protons both using solid targets made 100% of the element or water-based solutions of different concentrations. The data confirmed that all candidates emit signature PGs different from water (here used as a proxy for normal tissue), and that the gamma yield is directly proportional to the element concentration in the solution. Four specific gamma lines were detected for both ^31P (1.14, 1.26, 1.78 and 2.23 MeV) and ^63Cu (0.96, 1.17, 1.24, 1.326 MeV), while one for ^89Y (1.06 MeV). To provide a proof-of-principle of the proposed approach, using TOPAS Monte Carlo we investigated the correlation between the number of produced signature PGs and the proton range, and assessed range accuracy. The simulations indicate that the count of characteristic gammas is directly proportional to the proton range, reaching in some cases a saturation value around the tumor far-edge. The results also indicate that to achieve a range accuracy below the current value of 2-3 mm, the uncertainty on the PG count has to be below 5% for 31-Phosphorous and 63-Copper, or 10% for 89-Yttrium. In conclusion, we demonstrated that loading the tumor with a label element prior proton treatment, generates signature gammas that can be used to verify the beam range in vivo, reaching a potential accuracy below the actual value. This approach can be either used stand-alone or combined with other existing methodologies to further improve range resolution.